Routledge Philosophy GuideBook to Kripke and Naming and Necessity. - Noonan, Harold (Taylor and Francis, 2014)
Saul Kripke is one of the most important philosophers of the twentieth century. His most celebrated work, Naming and Necessity, makes arguably the most important contribution to the philosophy of language and metaphysics in recent years. Asking fundamental questions - how do names refer to things in the world? Do objects have essential properties? What are natural kind terms and to what do they refer? - he challenges prevailing theories of language and conceptions of metaphysics, especially the descriptivist account of reference, which Kripke argues is found in Frege, Wittgenstein and Russell,